2001
DOI: 10.1021/jp011588e
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of Phenyl Rings and Methylene Bisectors at the Free Surface of Atactic Polystyrene

Abstract: Atomistically detailed models of free-standing thin films and the bulk structure of amorphous atactic polystyrene have been produced by reverse mapping from equilibrated coarse-grained models. The bridging technique employed in the simulation allows the generation of a moderate sized atomistic system (six independent parent chains of C 400 H 402 , 4812 atoms) with a more reasonable computational effort than is required when all of the construction is performed on chains expressed with atomistic detail. Reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
61
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 24 publications
15
61
2
Order By: Relevance
“…10 The typical uncertainties in the surface energies in our method are (10 erg/cm 2 . 6 The plateau density, F 0 , is also close to the bulk density expected by considering the composition of the chain, and the correlation length, , is comparable to those obtained previously for other amorphous polymeric hydrocarbons. 44 Later on we will also compare our results for the aPP surface with those obtained by Mansfield and Theodorou.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…10 The typical uncertainties in the surface energies in our method are (10 erg/cm 2 . 6 The plateau density, F 0 , is also close to the bulk density expected by considering the composition of the chain, and the correlation length, , is comparable to those obtained previously for other amorphous polymeric hydrocarbons. 44 Later on we will also compare our results for the aPP surface with those obtained by Mansfield and Theodorou.…”
Section: Resultssupporting
confidence: 87%
“…[1][2][3][4][5] In general, it is reported that, for all systems investigated so far, side groups are found to orient outward and normal to the free surface. Simulation results 6,7 on selected homopolymers are in agreement with the experimental results by SFG. Recently, 5 SFG has also been used to study surfaces of random poly(ethylene-co-propylene) with a focus on understanding the effect of changing ethylene fraction on the surface structure.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Their finding is consistent with molecular dynamics simulations [45], and with earlier results from SFG spectroscopy [37,38]. All of these previous studies attribute the observed anisotropy entirely to the phenyl rings because of their highly anisotropic bonding.…”
supporting
confidence: 90%
“…Previous MD study on atactic polystyrene surface revealed that the methylene groups were weakly ordered and was able to explain why the dominant signal in the SFG spectra was from the side chain phenyl groups. 27 MD analysis in conjunction with SFG measurements helped in explaining the strong SFG signal associated with the ordering of poly(dimethylsiloxane) (PDMS) methyl groups in contact with the methyl head groups of the self-assembled monolayer. 28 In addition to polymer surfaces, MD has also been used to explain the SFG spectra of interfacial water 29 and aqueous solutions.…”
Section: ■ Introductionmentioning
confidence: 99%